Activism and radicalism in adolescence: an empirical test on age-related differences - Pfundmair, Michaela (Psychology, crime & law, 2021)
These days, political mobilization, particularly among young people, is on the rise. However, some of these people not only engage in legal and non-violent (activism) but also in illegal and violent actions (radicalism). In this work, we aimed to empirically explore these phenomena in greater detail, hypothesizing that younger (compared to older) adolescents are not only more prone to activism but also radicalism. We additionally aimed to investigate risk factors in this developmental period. In particular, we explored the possibility that social exclusion and a weak moral identity would make adolescents more readily express support for radicalism. In a study with four different Austrian high schools, activism and radicalism was assessed in mid- to late adolescents (14–19 years) using different validated measures. Moreover, we assessed participants’ moral identity and manipulated social exclusion. Results showed that participants in mid adolescence were more susceptible to activism and, in particular, radicalism than participants in late adolescence. Moreover, weak moral convictions revealed to be related to radicalism among mid-adolescents. Social exclusion did not moderate radicalism in adolescents. Illuminating age-related differences in activism and radicalism, the current study contributes to an empirical foundation of radicalism research and may animate means of prevention in developmental populations.